Salmonella enterica Serovar Enteritidis and Typhymurium: Phenotypic, Molecular Detection and Sequencing of Quorum Sensing - Zainab Adil Ghani Chabuck (Journal of Global Pharma Technology, 2020)
Bacterial messaging and chatting, or Quorum sensing (QS) is a way that permitting the coordination behaviors of groups between many common bacterial pathogens. Objectives: Phenotypic detection of Quorum sensing production followed by Molecular Detection and Sequencing of its gene sdiA. Materials and Methods: A primers pair for PCR detection of sdiA gene of Salmonella enterica serovar enteritidis and typhymurium had been designed for its detection and followed by its sequencing for detection of mutation using automated sequencing. These were preceded by phenotypic detection of QS. Results: Quorum sensing produced by S. enterica was studied. Results revealed that homoserine lactone production causes the appearance of bacterial cells aggregation, which appears best after 4hours of incubation where it is representing a maximum concentration of homoserine lactone. In addition, sdiA gene is present in all isolates. Sequencing of sdiA gene from isolates of Salmonella enterica serovar enteritidis and typhymurium propose that there were 8 mutations in three isolates, also gave identity in a percentage of (98-99%) with standard strand according to NCBI web site. Keywords: Quorum sensing, Salmonella enterica, sdiA, sequencing.